Logbooks alone are not enough: initial experience with implementing a logbook for medical students in a clinical internship in gynecology and obstetrics - Jud, Sebastian; Cupisti, Susanne; Frobenius, Wolfgang; Benn, Sigrid; Winkler, Andrea; Antoniadis, Sophia; Beckmann, Matthias; Heindl, Felix (European Journal of Medical Research, 2020)
BACKGROUND: Logbooks are being increasingly widely used as a means of improving medical education and further training. They will in all probability continue to be mandatory in the Practical Year (PJ) in Germany even after the upcoming amendment of the Medical Licensing Regulations (ÄAppO). However, there are different approaches to their design and use, and these are also currently undergoing considerable change. This study for the first time examines and discusses the influence of logbooks on students' evaluation of a gynecology internship. METHODS: The study was based on a well-established two-part 1-week internship course, with initially unstructured morning classes on wards and duty areas, along with precisely planned afternoon classes with skills training by peer teachers and seminars supervised by duty-exempted physicians. The postgraduate lecturers were prepared for the introduction of the logbook in a special course, and the aim was to optimize morning classes by introducing learning objectives adapted to the respective locations. The effects over 38 weeks of practical training were examined in evaluations by 235 prospectively group-randomized students with and without logbooks (n = 166 and n = 66, respectively; three datasets were not evaluable). RESULTS: In the cohort comparison, the logbook group responded significantly more positively toward the internship at the start of the course (P = 0.046). In the final evaluation, however, medical supervision during the entire internship was rated significantly more poorly (P = 0.007). The logbook cohort also considered that guidance based on learning objectives was significantly worse, as was the extent to which wards and duty areas were prepared for the students (P = 0.001 and P = 0.029). CONCLUSIONS: Introducing a logbook to optimize clinical teaching in internships may raise expectations that cannot always be met. In addition to adapting the learning objectives to a general framework that is less favorable in comparison with the Practical Year, the least that is required appears to be simultaneous and continuous mentoring of the lecturers, as well as an increase in staffing resources.
CRIS-Team Scopus Importer:2020-05-26
Keywords: Gynecology; Internship; Logbook; Teaching